Smart Home System controlling by Wireless Network Technology Sensors and android Application with the concept of Internet of Things. - Iambandit, Siriwan (Science Technology and Innovation Journal, 2020)
The purpose of this special problem is to develop an intelligent energy management system focusing on power usage in a room with an embedded computer. This is a system which monitors the power used in a room via infrared detector is activated, the system will turn on electrical equipment and continue to monitor them. The system will measure and store the electric energy data that’s used by those electrical appliances, the results are then displayed though an Android operating system interface. The results from this developed system are useful to users when conducting analysis of data for potential energy saving processes in the future.